A New Species of Rumex from India - Vaid, K. M.; Naithani, H. B. (Indian Forester, 1979)
A species of Rumex new to science, Rumex punjobensis Vaid & Naithani from Amritsar (Punjab) India, is described. This species is called to Rumex crispus Linn., but differs in having long petiole and cordate base of radical leaves, dentate margin of fruiting sepals and all bisexual flowers. This taxon is named after the state ie., Punjab from where it was first collected.